Principal Leadership in Managing Human Resources to Improve School Performance - Usfandi Haryaka (PT. Anagata Sembagi Education, 2025)
Leadership has an important role in determining the success of an educational institution. This research focuses on the strategic role of the principal's leadership in managing human resources (HR) to improve overall school performance. Principals have an important responsibility in creating a work environment that supports, motivates and empowers teachers and staff to achieve the school's vision and mission. This research identifies various leadership approaches, such as the development of a collaborative work culture, effective conflict management, providing constructive feedback, and implementing training programs and continuous professional development. This research method uses a qualitative approach with a case study design to explore in depth how principals implement leadership strategies in managing human resources (HR) to improve school performance. The results showed that strong, strategic and visionary leadership of school principals is a fundamental element in driving overall school success. Effective principals not only act as administrative leaders, but also as prime movers who are able to motivate, inspire and empower all elements of the school. By promoting a clear vision and a collaborative approach, principals are able to create a healthy, harmonious and innovative work culture. Effective human resource management is one of the key aspects in this success. The implications of this study emphasize that principals need to continue developing their leadership competencies through professional training and mentoring. In addition, education policy should support a leadership system that is oriented towards strengthening human resources to improve the quality of education in schools.